Analisis Perbandingan Kinerja Keuangan Pemerintah Daerah Tahun Anggaran 2012-2016 (Studi Pada Empat Kabupaten Pemekaran Provinsi Sulawesi Utara) - Kopong, Lusiana selly (Universitas Sam Ratulangi, 2019)
The results showed that the financial performance of the four pemekaran districts in North Sulawesi Province, the financial district of Southeast Minahasa Regency was ranked first with 61.30% achievement, Siau Biaro Tagulandang was ranked second 60.71%, Bolaang Mongondow Selatan District at third place 60.47 % and Bolaang Mongondow Timur Regency in fourth place 56.81%. That’s mean there was not significance difference of financial performance of local government on fourth provinces at North Sulawesi RegionalKeywords: Financial Performance Racio, Financial Performance of Local Government